2017
DOI: 10.1016/j.eswa.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Data mining methods for knowledge discovery in multi-objective optimization: Part B - New developments and applications

Abstract: The first part of this paper served as a comprehensive survey of data mining methods that have been used to extract knowledge from solutions generated during multi-objective optimization. The current paper addresses three major shortcomings of existing methods, namely, lack of interactiveness in the objective space, inability to handle discrete variables and inability to generate explicit knowledge. Four data mining methods are developed that can discover knowledge in the decision space and visualize it in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…It has furthermore been suggested that parallel coordinates cannot display certain kinds of information and should be complemented (e.g., with spatial representations) for a more complete representation of alternatives (Xiao et al, 2007). Kok (1986), Sato et al (2015) and Bandaru et al (2017b) point out that when DMs only have a vague understanding of their preferences, it may be easier to specify loose ranges of preferences in the objective space, rather than exact points of preferences. The action of "brushing" available in interactive parallel coordinates charts addresses this issue.…”
Section: Interfaces For Multiobjective Interactive Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has furthermore been suggested that parallel coordinates cannot display certain kinds of information and should be complemented (e.g., with spatial representations) for a more complete representation of alternatives (Xiao et al, 2007). Kok (1986), Sato et al (2015) and Bandaru et al (2017b) point out that when DMs only have a vague understanding of their preferences, it may be easier to specify loose ranges of preferences in the objective space, rather than exact points of preferences. The action of "brushing" available in interactive parallel coordinates charts addresses this issue.…”
Section: Interfaces For Multiobjective Interactive Optimizationmentioning
confidence: 99%
“…The user can filter the polylines to display only those of interest by "brushing" the desired axes (Heinrich and Weiskopf, 2013;Bandaru et al, 2017b). The ability to display only the solutions which satisfy desired values on the different axes is a common response to the problem of cluttering, which causes parallel coordinates to become unreadable when too many lines are present (Johansson and Forsell, 2016;Li et al, 2017).…”
Section: Filtering Solutions and Criteriamentioning
confidence: 99%
“…identifying new market segments of customers or detecting e-commerce fraud). Data mining techniques found in the review include Self-Organising Maps (SOM) (Kohonen, 1995) which provide a visual map of data dependencies and Flexible Pattern Mining (FPM) (Bandaru et al, 2017) which aims at extracting patterns of rules within a given data set.…”
Section: Data Miningmentioning
confidence: 99%
“…In this module, we use the recently proposed flexible pattern mining (FPM) [35] approach to extract rules that distinguish the obtained trade-off solutions from the other feasible solutions obtained during the optimization process. FPM works on the same principle as frequent itemset mining that is used often on market basket data.…”
Section: Knowledge Extractormentioning
confidence: 99%